Ammonia: The molecule for establishing 14N and 15N absolute shielding scales and a source of information on nuclear magnetic moments - Makulski, Włodzimierz (2022)
Multinuclear Nuclear Magnetic Resonance (NMR) studies of the gaseous mixtures 3He/14NH3 and 3He/15NH3 are reported. Precise analysis of the 3He, 14N, 15N, and 1H resonance frequencies show a linear dependence on the gas density. Extrapolation of these results to the zero-pressure limit gives ν0(1H), ν0(14N), and ν0(15N) resonance frequencies of the isolated ammonia molecule at 300 K. The analogous value for 3He atoms in gaseous mixtures ν0(3He) was measured as well. The application of a new scheme to introduce the most important electronic effects on NMR shieldings, together with highly accurate quantum chemical shielding calculations, allows the 14/15N and 1H shielding of the isolated ammonia molecule to be obtained with the greatest accuracy and precision. For the first time, these studies were carried out on ammonia within the so-called four-component relativistic framework. The NMR frequency comparison method provides an approach for determining the 14N and 15N nuclear magnetic moments. The new shielding parameters in ammonia were used for re-evaluation of the entire nitrogen absolute shielding scale. Additionally, the absolute shielding values of several gaseous compounds and secondary reference substances in liquids were presented. It was established that 14N and 15N absolute shielding constants in 14NH3 and 15NH3 are very similar and only differ by less than 0.01 ppm, which is not usually measurable in NMR experiments. Precise calculations of 14N and 15N dipole moments were also made from these accurate shielding values.